A completed audit to reduce hospital outpatients non-attendance rates. Issue 1 (1st January 2000) - Gatrad, A R
Abstract : An audit loop for patients failing to attend a paediatric outpatient department was completed by repeating the analysis three years after interventions were put into place. The 1995 study had shown non-attendance for clinic visits was 34%, varying from 32.5% for Europeans and 50% for Asian patients. A follow up study in 1998 showed a fall to 12.04% and 13.5%, respectively, with an overall rate of 12.3%. The Manor Hospital NHS Trust had the lowest non-attendance rate of the 30 hospitals in the West Midlands region for the year 1996–7.